2019
DOI: 10.3389/fnins.2018.01014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Traumatic Brain Injury on Neurogenesis

Abstract: New neurons are generated in the hippocampal dentate gyrus from early development through adulthood. Progenitor cells and immature granule cells in the subgranular zone are responsive to changes in their environment; and indeed, a large body of research indicates that neuronal interactions and the dentate gyrus milieu regulates granule cell proliferation, maturation, and integration. Following traumatic brain injury (TBI), these interactions are dramatically altered. In addition to cell losses from injury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 120 publications
(126 reference statements)
2
38
1
Order By: Relevance
“…This study demonstrates that maternal nicotine exposure in prepregnancy, pregnancy, and lactation stages impairs the behavioral performance, hippocampal neurogenesis, and microglial activation in the offspring. Our data support the view that maternal nicotine exposure produces an adverse effect on the offspring and is detrimental to the naturally occurring neurogenetic processes in the adult brain (Ngwenya and Danzer, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…This study demonstrates that maternal nicotine exposure in prepregnancy, pregnancy, and lactation stages impairs the behavioral performance, hippocampal neurogenesis, and microglial activation in the offspring. Our data support the view that maternal nicotine exposure produces an adverse effect on the offspring and is detrimental to the naturally occurring neurogenetic processes in the adult brain (Ngwenya and Danzer, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…we have not ruled out the possibility that some of the EdU+ cells distant to the injury migrated 230 from areas closer to the wound. Similar effects at a distance from an injury have been observed 231 in rodent models of TBI (Urrea et al, 2007, Ngwenya andDanzer, 2018).…”
supporting
confidence: 69%
“…This latter phenomenon of granule cell-to-granule cell connectivity has been termed a recurrent excitatory circuitry [79,90]. This aberrant circuitry produces excitatory drive that can both promote and facilitate the spread of seizure activity [91,92], and more recent studies further support the role of this aberrant circuitry in epileptogenesis [93][94][95], including the involvement of injuryinduced atypical astrocytes [96]. Interestingly, a study also showed that during pilocarpine-induced epileptogenesis, the radial glial-like processes in the dentate gyrus upregulate the expression of CCR2.…”
Section: Astrocytes and Pte: Support Cell Inflammatory Mediator Ormentioning
confidence: 98%